The power mapping tool: A method for the empirical research of power relations - Schiffer, Eva (International Food Policy Research Institute, 2007)
This paper presents an innovative participatory method to visualize, discuss and analyze the power of different actors in a given governance field. The Power Mapping Tool was first used to analyze the governance effects of Community-Based Natural Resource Management (CBNRM) in Namibia. This example is presented as a case study to show how the method works: The actors involved are represented by board game figures that are characterized through “range-of-action-cards” and put on wooden “power towers” to show their power in the governance field. The result is a three dimensional sketch that provides quantitative data and guides the qualitative discussion about reasons for and effects of the power of different actors. In the case of Namibian CBNRM Power Mapping helped to understand how power indeed had been devolved from the national to the local level. However, on the community level elite-capture was seen as a serious problem. In this research the Power Mapping Tool proved to be easy to use with a very diverse mix of interview partners and provided not only a wealth of data but also increased the interviewees’ understanding of their own situation.